Changes in blood monocyte Toll‐like receptor and serum surfactant protein A reveal a pathophysiological mechanism for community‐acquired pneumonia in patients with type 2 diabetes. Issue 2 (February 2016) - Que, Y.; Shen, X.
Abstract : Background: The lung is one of the target organs of microangiopathy in diabetes mellitus (DM); patients with type 2 diabetes mellitus (T2DM) are vulnerable to pneumonia, and a variety of pathophysiological mechanisms has been described. Aim: This study aimed to determine the pathophysiological mechanism of community‐acquired pneumonia (CAP) in T2DM patients. Methods: A total of 90 individuals was included in this study comprised of three groups ( n = 30): healthy control, T2DM and T2DM+ CAP groups. Toll‐like receptor (TLR)2 and 4 protein and messenger RNA expression in peripheral blood monocytes(PBMC) was assessed by western blot and reverse transcription–polymerase chain reaction, respectively, and surfactant protein A (SP‐A) levels were examined in serum samples by enzyme‐linked immunosorbent assay. Results: In T2DM and T2DM+CAP groups, levels of both TLR2/4 protein and mRNA in PBMC were decreased compared with controls ( P <0.05), with lower levels observed in the T2DM+CAP group in comparison with T2DM patients ( P <0.05). The serum SP‐A levels in T2DM+CAP individuals were significantly higher than the values obtained for T2DM patients ( P <0.05). It also showed apparent increases when compared with that in controls although no statistical significance was detected. Conclusion: In T2DM patients with pneumonia, TLR2/4 levels in PBMC and serum SP‐A were altered, maybe playing an important role in the susceptibility to pneumonia in T2DM patients.